Steiner cephalometric analysis discrepancies between conventional and digital methods using Cephninja® application software - Gayatri, Gita; Harsanti, Andriani; Zenab, Yuliawati; Sunaryo, Iwa Rahmat (Padjadjaran Journal of Dentistry, 2016)
Introduction: Cephalometric analysis have been widely used in orthodontics. The analysis can be conducted in two methods: conventional and digital methods. Practitioners prefer using computerized cephalometric analysis due to its simplicity and less time-consuming compared to manual or conventional method. The objective of this study was to identify discrepancies between Conventional Steiner cephalometric analysis and digital cephalometric analysis using CephNinja® Application. This study was an experimental in vivo study with descriptive and comparative approach. Methods: Thirty two negative and digital cephalograms were traced manually using Steiner analysis and digitally using CephNinja® software application. Tracing results of manually analyzed cephalogram and digitally analyzed cephalogram were then compared. Results: There were no distinguished discrepancies between the tracing results of both manually and digitally analyzed cephalogram using Steiner analysis. Conclusion: there was no significant difference of steiner cephalometric analysis conducted using conventional tracing and digital method using CephNinja® application software.